Edukasi Pengelolaan Sampah Terintegrasi dengan Program NTB Zero Waste: Studi Kasus di Kecamatan Praya - Rohman, Ade; Kamal, Mustafa (Lembaga Publikasi Ilmiah Nusantara, 2025)
The NTB Zero Waste program is a government initiative aimed at creating a clean and sustainable environment through integrated waste management. This study seeks to educate the community of Praya District on effective waste management aligned with the NTB Zero Waste program. The approach involves socialization, training, and mentoring the community, focusing on sorting organic and inorganic waste, transforming waste into economically valuable products, and applying the 3R principles (reduce, reuse, recycle). The results show an increase in community awareness regarding independent waste management, enhanced participation in cleanliness programs, and a reduction in unmanaged waste. These findings indicate that continuous education and collaboration with government programs can positively impact local waste management. This study can serve as a reference for implementing similar programs in other regions.